2007
DOI: 10.3748/wjg.v13.i2.264
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of long term cyclic administration of the poorly absorbed antibiotic Rifaximin in symptomatic, uncomplicated colonic diverticular disease

Abstract: AIM:To comparatively evaluate the long term efficacy of Rifaximin and dietary fibers in reducing symptoms and/or complication frequency in symptomatic, uncomplicated diverticular disease. METHODS:307 patients (118 males, 189 females, age range: 40-80 years) were enrolled in the study and randomly assigned to: Rifaximin (400 mg bid for 7 d every month) plus dietary fiber supplementation (at least 20 gr/d) or dietary fiber supplementation alone. The study duration was 24 mo; both clinical examination and symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 30 publications
2
76
0
9
Order By: Relevance
“…Rifaximin is a non-absorbable antibiotic derived from the macrolide rifamycin with demonstrated efficacy in inducing remission in patients with active C [15,16,17,18,19], in reducing stool frequency, rectal bleeding and sigmoidoscopic score and achieving remission in patients with U [20,21], in obtaining symptoms relief in patients with uncomplicated D [22,23,24] or I with or without constipation [25]. Rifaximin has a strong in vitro antimicrobial effect against aerobic and anaerobic Gram-positive and Gram-negative bacteria, including several pathogens such as Escherichia coli , Enterobacteriaceae and Clostridium difficile [26]; beyond this expected activity, rifaximin is supposed to have additional effects on the gut microbiota about which very little is known.…”
Section: Introductionmentioning
confidence: 99%
“…Rifaximin is a non-absorbable antibiotic derived from the macrolide rifamycin with demonstrated efficacy in inducing remission in patients with active C [15,16,17,18,19], in reducing stool frequency, rectal bleeding and sigmoidoscopic score and achieving remission in patients with U [20,21], in obtaining symptoms relief in patients with uncomplicated D [22,23,24] or I with or without constipation [25]. Rifaximin has a strong in vitro antimicrobial effect against aerobic and anaerobic Gram-positive and Gram-negative bacteria, including several pathogens such as Escherichia coli , Enterobacteriaceae and Clostridium difficile [26]; beyond this expected activity, rifaximin is supposed to have additional effects on the gut microbiota about which very little is known.…”
Section: Introductionmentioning
confidence: 99%
“…65 Multiple studies have shown that rifaximin can effectively improve symptoms and maintain periods of remission in patients with uncomplicated diverticular disease, while also being well tolerated. [66][67][68][69][70] …”
mentioning
confidence: 99%
“…Рифаксимин-α используется в Италии с 1987 г. Альфа Нормикс не вызывает перекрест-ной бактериальной резистентности. Альфа Нормикс эффективен и безопасен при ежемесячном курсовом и длительном (до 4 лет) применении [21,22].…”
Section: дивертикулярная болезнь с клиническими проявления-ми (неослоunclassified
“…4) [23]. В рамках исследования Colecchia et al (многоцентровое проспек-тивное рандомизированное контролируемое открытое клиническое исследование у пациентов с симптоматиче-ской неосложненной дивертикулярной болезнью ободоч-ной кишки) [24] было убедительно показано, что цикличе-ское применение рифаксимина-α (400 мг х 2 р/день 7 дней/месяц) в сочетании с пищевыми волокнами (мин. 20 г/день) эффективнее терапии только пищевыми волокна-ми в уменьшении симптомов у пациентов с симптомати-ческой неосложненной дивертикулярной болезнью.…”
Section: дивертикулярная болезнь с клиническими проявления-ми (неослоunclassified